Proceedings of the third IUMRS International Conference on Advanced Materials, Sunshine City, Ikebukuro, Tokyo, Japan, August 31 - September 4, 1993 - International Conference on Advanced Materials (3rd : 1993 : Tokyo, Japan); International Union of Materials Research Societies (Amsterdam : Elsevier, 1994)
v.19A. Superconductors, surfaces and superlattices -- v.19B. Frontiers in materials science and engineering